2018
DOI: 10.1186/s12931-018-0935-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and lung injury in an ovine model of fluid resuscitated endotoxemic shock

Abstract: BackgroundSepsis is a multi-system syndrome that remains the leading cause of mortality and critical illness worldwide, with hemodynamic support being one of the cornerstones of the acute management of sepsis. We used an ovine model of endotoxemic shock to determine if 0.9% saline resuscitation contributes to lung inflammation and injury in acute respiratory distress syndrome, which is a common complication of sepsis, and investigated the potential role of matrix metalloproteinases in this process.MethodsEndot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…The primary treatment outcomes focused on tissue oxygen delivery and repayment of oxygen debt (27), which are translatable as patient-outcome measures to guide Patient Blood Management. Although aggressive fluid resuscitation may adversely impact microvascular function via glycocalyx degradation, causing increased lung injury after severe shock (28,29), histological assessment of lung tissue and the wet:dry ratio confirmed that fluid-associated lung injury was minimal. Importantly, the resuscitation protocol restored both macrocirculatory and microcirculatory parameters (6,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 88%
“…The primary treatment outcomes focused on tissue oxygen delivery and repayment of oxygen debt (27), which are translatable as patient-outcome measures to guide Patient Blood Management. Although aggressive fluid resuscitation may adversely impact microvascular function via glycocalyx degradation, causing increased lung injury after severe shock (28,29), histological assessment of lung tissue and the wet:dry ratio confirmed that fluid-associated lung injury was minimal. Importantly, the resuscitation protocol restored both macrocirculatory and microcirculatory parameters (6,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 88%
“…The lung histopathology score was calculated according to the histopathological severity of the analyzed sections of each lung (six separate random fields per tissue section). The scores were assigned as follows: normal = 0; minor = 1; mild= 2; intermediate = 3; and severe = 4 ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…4 µm thick deparaffinized sections were stained with hematoxylin and eosin (H&E) and analyzed at 10 × magnification. The histology sections were evaluated for metastatic lesions, morphological changes and necroinflammation according to a modified histology activity index ( Gibson-Corley et al, 2013 ; Passmore et al, 2018 ). The sections were scored by a cumulative quantitative score of 0–4 representing; 0—Normal histological alterations, 1–3—Mild/moderate/severe and 4- Extreme histological alterations ( Tables 1 and 2 ).…”
Section: Methodsmentioning
confidence: 99%